THE INFLUENCE OF ROE, ROI, NPM, AND EPS ON SHARE PRICES OF PROPERTY AND REAL ESTATE COMPANIES 2016-2022 - Siahaan, Boxer; Pratama, Ayang; Lubis, Yeti Meliany (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to determine the effect of ROE, ROI, NPM, and EPS on the 2016 - 2022 Property and Real Estate Company Stock Prices. This research was obtained using a purposive sampling method, in which the researcher made the best assessment to fulfill what had been determined. And this research with a quantitative research approach. The sampling technique in this study amounted to 13 companies. This study uses documentation data collection techniques using secondary data. The data analysis technique used in this study is the Classical assumption test, Multiple Linear Analysis, Hypothesis Testing, and Coefficient of Determination using the SPSS version 25 application. More over, the results show that ROE, ROI, and EPS significantly affect the stock prices of property and real estate companies. Furthermore, NPM does not significantly affect the Share Price of Property and Real Estate Companies. Moreover, the results of ROE, ROI, NPM, and EPS simultaneously significantly affect the Stock Price of Property and Real Estate companies.